2020
DOI: 10.1002/ijgo.13303
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occult microscopic endometriosis in clinically negative peritoneum during laparoscopy for chronic pelvic pain

Abstract: Objective: To determine the prevalence of occult microscopic endometriosis in patients with chronic pelvic pain and negative laparoscopy. Methods: A retrospective cross-sectional study included women who underwent laparoscopic evaluation for chronic pelvic pain by three fellowship-trained gynecologic surgeons at a community hospital from January 2011 to December 2016. The aim was to evaluate the prevalence of microscopic endometriosis in this population. Results: In 142 patients with clinically negative perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Gubbels et al . found OME in 39% of patients with clinically negative peritoneum on laparoscopy 165 and in the study by Gratton et al ., 58% (7/17) of people with visually normal pelvises had evidence of endometriosis on histology 144 . The ability of histology to detect endometriosis that is not visibly apparent makes it a remarkably valuable tool for diagnosis.…”
Section: Diagnostic Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Gubbels et al . found OME in 39% of patients with clinically negative peritoneum on laparoscopy 165 and in the study by Gratton et al ., 58% (7/17) of people with visually normal pelvises had evidence of endometriosis on histology 144 . The ability of histology to detect endometriosis that is not visibly apparent makes it a remarkably valuable tool for diagnosis.…”
Section: Diagnostic Methodsmentioning
confidence: 76%
“…far viewing distance at time of laparoscopic lesion identification, size and location of biopsies taken), which may have contributed to their high rate of OME detection 164 . Gubbels et al found OME in 39% of patients with clinically negative peritoneum on laparoscopy 165 and in the study by Gratton et al, 58% (7/17) of people with visually normal pelvises had evidence of endometriosis on histology 144 . The ability of histology to detect endometriosis that is not visibly apparent makes it a remarkably valuable tool for diagnosis.…”
Section: Histologymentioning
confidence: 94%
“…With intensive pathologic evaluation, we subsequently reported an increased premenopausal prevalence of benign ectopic growths, including ES (37%), endometriosis (EM) (32%), paratubal cysts (47%), and Walthard’s nests (ectopic urothelial cell growths) (29%) in women with at-risk tissues age 31-50, with ES prevalence increasing to 66% after menopause, in contrast to a decrease in EM (5%), while 89% of post-menopausal specimens had some type of ectopic lesion and various lesion types could be present in the same patient [2]. Another recent study reporting EM in 39% of random biopsies of patients with chronic pelvic pain also found much higher prevalence than expected [3]. Sampling bias is the likely explanation for retrospective studies reporting an association of these benign peritoneal cavity cellular implants with malignancy [46], since the large majority of patients undergoing surgery for benign conditions do not have a histologic evaluation of all tissues as thorough as that performed for malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Around half of women who have clinically suspected endometriosis undergo surgery to confirm the diagnosis [ 6 ]. Clinical suspicion of endometriosis is an inconsistent predictor of disease; of women undergoing laparoscopy for suspected endometriosis, 18–77% have surgically confirmed disease [ 7 ], although recent evidence suggests that the rates of microscopic endometriosis in women with “negative laparoscopy” may be up to 39% [ 8 ]. There is a strong need for a reliable non-invasive diagnostic tool to reduce the need for laparoscopy to diagnose or exclude endometriosis.…”
Section: Introductionmentioning
confidence: 99%